Benzoxazinoid and indoxyl glycosides from Wrightia religiosa. (August 2018) - Sahakitpichan, Poolsak; Chimnoi, Nitirat; Srinroch, Chutima; Ruchirawat, Somsak; Kanchanapoom, Tripetch
Graphical abstract: (2 S )-2- O -β-d -Glucopyranosyl-2H-1, 4-benzoxazin-3(4H)-one (2 ) and indoxyl 3- O -β-d -apiofuranosyl-(1 → 6)-β-d -glucopyranoside (4 ) were isolated from Wrightia religiosa . Highlights: A benzoxazinoid with (2 S )-configuration was isolated for the first time from natural source. A new indoxyl diglycoside was obtained from Wrightia religiosa . Benzoxazinoids were firstly reported from Wrightia religiosa of the family Apocynaceae. Abstract: A new class of secondary metabolites of the family Apocynaceae, benzoxazinoid, was reported for the first time from Wrightia religiosa . A new benzoxazinoid glycoside, (2 S )-2- O -β-d -glucopyranosyl-2 H -1, 4-benzoxazin-3(4 H )-one (2 ) and a new indole diglycoside, indoxyl 3- O -β-d -apiofuranosyl-(1 → 6)-β-d -glucopyranoside (4 ) were isolated, together with twelve known compounds, including benzoxazinoid glycosides (1, 3 ), simple aromatic glycosides (5 –8 ), a lignan glycoside (9 ), flavonol glycosides (10 –13 ) and a megastigmane glucoside (14 ). The structure elucidation of these compounds was based on analyses of physical and spectroscopic data including 1D and 2D NMR experiments. A benzoxazinoid with (2 S )-configuration was isolated for the first time from natural source.